A comparative study of the efficiency of chemical coagulation and electrocoagulation methods in the treatment of pharmaceutical effluent. (April 2020) - Padmaja, K.; Cherukuri, Jyotsna; Anji Reddy, M.
Highlights: Chemical coagulation using alum and ferric chloride reduced TDS in pharmaceutical effluent by 14.05% and 26.3% respectively. Electrocoagulation with Fe- Al electrode assembly reduced TDS and COD by 91.5% and 92.3%, making it more efficient than chemical coagulation. The removal efficiency was high using a current of 0.04 amperes and a time interval of 15 min with Fe- Al electrode assembly. Development of in-situ coagulants and no sludge formation makes Electrocoagulation cost effective and environment friendly. Abstract: Hyderabad city is an emerging pharmaceutical hub of India. Pharmaceutical effluent contains many organic and inorganic compounds which need to be treated before discharging into natural water bodies or municipal sewers. The disposal of these wastes should be done in a safe, secure and aesthetic way failing which, results in harmful effects on human, plant and animal life. In the present study effluent from a pharmaceutical industry in Hyderabad, manufacturing Active Pharmaceutical Ingredients (APIs) and solid oral dosage forms is analyzed. It was found to contain large amounts of Dissolved solids, COD, Suspended solids, chlorides and colour. In this paper a comparative study of Chemical coagulation and Electrocoagulation in treating the effluent is made to find a more efficient and cost-effective technology. The results showed that though chemical coagulation has brought a considerable decrease in percentage of COD, suspended solids and chlorides, but the extent of decrease in the Total Dissolved Solids (TDS) is only 14.05 % using Alum and 26.3 % with FeCl3 . Whereas electrocoagulation method which has reduced both COD and TDS to greater extent (92.3 % & 91.5 %) proved more efficient with Fe-Al assembly using a lowest current of 0.04 A at a time interval of 15 min. The coagulant consumption is also less in eletrocoagulation compared to chemical coagulation rendering it a cost effective technology.